Cold-Azurin, a New Antibiofilm Protein Produced by the Antarctic Marine Bacterium Pseudomonas sp. TAE6080 - Caterina D’Angelo; Marika Trecca; Andrea Carpentieri; Marco Artini; Laura Selan; Maria Luisa Tutino; Rosanna Papa; Ermenegilda Parrilli (Marine Drugs, 2024)
Biofilm is accountable for nosocomial infections and chronic illness, making it a serious economic and public health problem. Staphylococcus epidermidis, thanks to its ability to form biofilm and colonize biomaterials, represents the most frequent causative agent involved in biofilm-associated infections of medical devices. Therefore, the research of new molecules able to interfere with S. epidermidis biofilm formation has a remarkable interest. In the present work, the attention was focused on Pseudomonas sp. TAE6080, an Antarctic marine bacterium able to produce and secrete an effective antibiofilm compound. The molecule responsible for this activity was purified by an activity-guided approach and identified by LC-MS/MS. Results indicated the active protein was a periplasmic protein similar to the Pseudomonas aeruginosa PAO1 azurin, named cold-azurin. The cold-azurin was recombinantly produced in E. coli and purified. The recombinant protein was able to impair S. epidermidis attachment to the polystyrene surface and effectively prevent biofilm formation.